SAA as Inflammatory Marker in Rheumatoid Arthritis: Study on Standard Therapy and Moringa Extract - Yan Ajie Nugroho; B. Rina A. Sidharta; Lusi Oka Wardhani; JB. Suparyatmo; MI. Diah Pramudianti (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Rheumatoid arthritis is a chronic systemic inflammatory autoimmune disorder characterized by persistent joint inflammation leading to cartilage and bone damage, disability, and systemic complications. The levels of APR such as SAA serum increase during synovitis. Previous studies have demonstrated the anti-inflammatory effect of M.oleifera leaf extract in the treatment of RA in animals; however, research data on humans remain limited. An experimental study on pre- and post-treatment of 40 RA patients was carried out by dividing subjects into 2 groups, including a standard therapy group and a standard therapy group added with M.oleifera leaf extract. The research was conducted at Dr. Moewardi Hospital, Surakarta from October 2020 to January 2021. The SAA levels were measured using ELISA. Paired T-test was used to analyze the differences in mean SAA levels before and after treatment. There was a significant difference between pre-treatment (346.57±54.40 ng/mL) and post-treatment (314.77±37.40 ng/mL) SAA levels in the standard therapy group added with M.oleifera leaf extract with p=0.01. Pre-treatment and post-treatment SAA levels in the standard therapy group were 322.68±87.01 ng/mL and 302.93±86.51 ng/mL, respectively with p=0.04. The mean of delta SAA in the standard therapy group added with M.oleifera leaf extract (-31.81±4.04 ng/mL) was greater than delta SAA in the standard therapy group (-19.75±4.07 ng/mL) with p=0.26. There was a significant decrease in SAA levels in RA patients on standard therapy and M. oleifera leaf extract.